Determinant Factors of Rice Paddy Land Conversion into Oil Palm Plantations and Strategies for Controlling It in Muara Padang Sub-District, Banyuasin Regency - Subandi, Asep; Wildayana, Elisa; Yamin, Muhammad (Kadiri University - Faculty of Agriculture, 2026)
Indonesia is an agrarian country where agricultural land plays an important role in ensuring food security. However, the increasing conversion of paddy fields into oil palm plantations has raised concerns regarding the long-term sustainability of rice production in major rice-producing regions. This study aims to analyze the process of paddy land conversion into oil palm plantations, identify the factors influencing farmers’ decisions, and formulate strategies to control land conversion in Muara Padang Sub-district, Banyuasin Regency, South Sumatra, Indonesia. The study employed a mixed-methods approach combining field surveys, structured interviews, binary logistic regression analysis, and SWOT analysis. A total of 92 farmers were selected as respondents using the Slovin formula with a 10% margin of error. The respondents were 46 rice farmers and 46 oil palm farmers, selected through quota sampling. The results indicate that land conversion occurs through several stages, including land evaluation, economic and social considerations, and land conversion implementation. Binary logistic regression analysis shows that farm income significantly influences farmers’ decisions to convert paddy fields into oil palm plantations (p = 0.025). The model demonstrates good fit based on the Hosmer–Lemeshow test (p = 0.764) and explains 91.9% of the variation in land conversion decisions (Nagelkerke R² = 0.919). The SWOT analysis places the land conversion control strategy in Quadrant I (Strength–Opportunity), indicating that internal strengths can be utilized to maximize existing opportunities. These findings suggest that improving rice farming productivity, strengthening farmer institutions, and providing economic incentives are essential to maintain sustainable paddy land and support national food self-sufficiency. This study contributes to the understanding of farmers’ land-use decisions and provides strategic policy recommendations for controlling agricultural land conversion in rice-producing regions.